34 The diagnostic and therapeutic pathway of the patient with SCA: Nursing&Tech assistance. (8th December 2021) - Santucci, Stefano; Franchetti, Domenico; Emanuelli, David; Cerulli, Martina; Marcotuttli, Sara; Santucci, Matteo; Gasperini, Vittorio
Abstract: Cardiomyopathies to be the first cause of death. The patient who suffers from acute heart disease, after clinical evaluation, is subjected to a diagnostic–therapeutic process that involves several professional figures which include the doctor and the ambulance nurse, the doctor and all the emergency room staff who accept the patient and, if the clinical indication is oriented towards a vascular occlusion disease, the doctor and the technical-nursing team of the haemodynamics service activated in urgency. To diagnose with certainty the presence of vascular disease we make use of diagnostic systems that use ionizing radiation; the haemodynamics team thus finds itself operating not only in urgent conditions but also in dangerous conditions due to the presence of ionizing radiation. Nursing and technical staff need additional skills to be able to take on roles from basic care to emergency electric shock resuscitation. The purpose of this work is to illustrate the phases of the activity that stabilize the treatment in the hemodynamics room from the acute phase to the patient.